2021
DOI: 10.3390/v13101971
|View full text |Cite
|
Sign up to set email alerts
|

Viral Decoys: The Only Two Herpesviruses Infecting Invertebrates Evolved Different Transcriptional Strategies to Deflect Post-Transcriptional Editing

Abstract: The highly versatile group of Herpesviruses cause disease in a wide range of hosts. In invertebrates, only two herpesviruses are known: the malacoherpesviruses HaHV-1 and OsHV-1 infecting gastropods and bivalves, respectively. To understand viral transcript architecture and diversity we first reconstructed full-length viral genomes of HaHV-1 infecting Haliotis diversicolor supertexta and OsHV-1 infecting Scapharca broughtonii by DNA-seq. We then used RNA-seq over the time-course of experimental infections to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
4
10
0
Order By: Relevance
“…By tracing ADAR hyper-editing along OsHV-1 infection in C. gigas , we demonstrated that in the early stage of infection host RNAs are more impacted than viral RNAs, with viral-directed editing increasing along the time course and suggesting that at later stages ADAR1 will mostly target viral dsRNAs. This increase is in agreement with data reported demonstrated for OsHV-1 infection in S. broughtonii ( 9 ), and likely mirrors the different abundances of viral and host dsRNAs during infection, with the latter increasing as a consequence of sense–antisense gene pair cotranscription ( 9 ). Next, we showed that host hyper-editing levels varied along each experiment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…By tracing ADAR hyper-editing along OsHV-1 infection in C. gigas , we demonstrated that in the early stage of infection host RNAs are more impacted than viral RNAs, with viral-directed editing increasing along the time course and suggesting that at later stages ADAR1 will mostly target viral dsRNAs. This increase is in agreement with data reported demonstrated for OsHV-1 infection in S. broughtonii ( 9 ), and likely mirrors the different abundances of viral and host dsRNAs during infection, with the latter increasing as a consequence of sense–antisense gene pair cotranscription ( 9 ). Next, we showed that host hyper-editing levels varied along each experiment.…”
Section: Discussionsupporting
confidence: 91%
“…This likely indicates that OsHV-1 resistant and immuno-primed oysters are trained/prone for hyper-editing, even at early stages of infection. Differently, non-IP oysters rapidly reached the same hyper-editing levels of IP oysters at 12 hpi, suggesting that OsHV-1 is highly effective in stimulating hyper-editing, probably because of its peculiar transcriptional architectures ( 9 ). A considerable fraction of the oyster transcriptome (∼0.5%) was hyper-edited irrespective of the experiment or condition.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…OsHV-1 transcriptome map based on PacBio long reads (21). Moreover, our data illuminates interesting new aspects of the OsHV-1 transcription beyond the mere expression analysis.…”
Section: Discussionmentioning
confidence: 68%
“…specific miRNAs or transcripts ( 42)), whereas in malacoherpesvirus, RNA editing extensively impacted multiple transcripts. We previously showed that in OsHV-1, the RNA editing is concentrated within genomic hotspots, whereas in HaHV-1 these modifications are more evenly distributed across the genome (21). However, up to now, the extension of RNA editing was indirectly deduced tracing highly modified short reads, as a proxy of ADAR hyper-editing, whereas no approaches were undertaken to detect inosines.…”
Section: Malacoherpesviruses Together With Vertebrate Herpesviruses (...mentioning
confidence: 99%